The Effect of Resistance Band Exercise on Dynamic Balance among Older Adults in Gresik, Indonesia - Yeni Andriani; Endah Nurul Kumarijati; Suhartono; Hanim Nur Faizah (PT Pubsains Nur Cendekia, 2026)
Background: Decreased dynamic balance in the elderly may lead to injury and reduced independence. Resistance band exercise can improve muscle strength and postural stability. Aims: To determine the effect of resistance band exercise on the dynamic balance level of elderly residents at Panti Jompo Lestari, Gresik Regency. Methods: This study used a pre-experimental design with a one-group pre-test and post-test approach. The sample consisted of 26 elderly participants selected using the total sampling technique. Dynamic balance was measured using the Timed Up and Go Test (TUG). The intervention was conducted for four weeks with a total of eight sessions of resistance band exercise. Data were analyzed using the Wilcoxon test with a significance level of α ≤ 0.05. Results: The results showed that before the intervention, the majority of respondents (92.3%) were in the moderate decline dynamic balance category. After the intervention, most respondents (84.6%) were categorized as having mild decline dynamic balance. The Wilcoxon test result showed an p < 0.001 and correlation koefesien 0,917 indicating a significant effect of resistance band exercise on improving dynamic balance in the elderly. Conclusions: Resistance band exercise has a significant effect on improving dynamic balance among elderly residents at Panti Jompo Lestari, Gresik Regency.